Título Padrão: as transformações urbanas de São Paulo e seus debates na imprensa periódica na década de 1920 - Andrade, Ana Luíza Mello Santiago de (Em Perspectiva, 2019)
The present article seeks to present and analyze chronicles published by Plínio Barreto during the 1920s in the newspaper O Estado de S. Paulo, during the period in which various structural reforms and daily habits occurred. It is understood that the author acted as an intellectual who mediated the relation of the readership with the public works and promoted the idea of São Paulo as one of the metropolises of the world in the process of modernization. The purpose of this article is to understand both the process of modernization that took place in the city and the way the periodical press acted in a pedagogical way to teach the inhabitants how to enjoy modernity. In addition, it is noticed that Plínio Barreto used of the space in the Things of the City to articulate political projects. The intention is, therefore, to note the relationship of the newspaper with the city of São Paulo and its projection as cosmopolitan capital.